I have six nonlinear equations and six unknows, can I use Newton raphson method for this prob.

vkjadhav@iitb.ac.in

Ad

I hope you will find the answer here

http://uranus.ee.auth.gr/lessons/1/10.html

Posted on May 24, 2008

Ad

Hi,

A 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

The service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

Good luck!

Posted on Jan 02, 2017

Ad

Your scientific calculator is unable to solve complex equation with complex coefficients. You should try to solve by hand directly using the quadratic formula or by factoring the polynomial in z

failing that, another way would be to set z=x+iy, substitute this for z, carry out the algebra and try to separate real and imaginary parts. But your two equations will constitute a system of two quadratic equations. I am not aware of any general method to solve coupled nonlinear equations.

Good luck.

failing that, another way would be to set z=x+iy, substitute this for z, carry out the algebra and try to separate real and imaginary parts. But your two equations will constitute a system of two quadratic equations. I am not aware of any general method to solve coupled nonlinear equations.

Good luck.

Dec 20, 2012 | Casio FX-115ES Scientific Calculator

Put the calculator in Equation solving mode. Select F3:Solver. Enter your equation; use X as unknow (no need to use Theta, the name of the variable is irrelevant.) Besides if you use theta you will get a syntax error.

Jun 29, 2012 | Casio CFX 9850GB Plus Calculator

In equation mode, you have system of linear equations (3 unknown) you have polynomial (quadratic and cubic), and solver. Use the solver foe any type of equation (nonlinear, polynomial of order higher than 4, trigonometric, exponential, logs).

May 21, 2012 | Casio Scientific Calculator Fx-570 Fx570...

Hi janeth sabay,

Have a good day!!

Here is your needed example for Homogenous differential equation:

The equation is said to be homogeneous if P and Q are homogeneous functions of x and y of the same degree.

(1)We can test to see whether this first order equation is homogeneous by substituting . If the result is in the form f(v)i.e. all the x's are canceled then the test is satisfied and the equation is Homogeneous.

Example 1:(2)(3)There are no terms in x on the right hand side and the equation is Homogereous.Example 2:(4)(5)So the original equation is not homogeneous.Methods Of Solution.A solution can be found by putting y = vx on both sides of the equation:-

Example 3:Putting y - vx

Since y is a function of x so is v

Separating the variables

Integrating

Substituting (12) in equation (10)

I can suugest you also to visit this site for more examples http://www.codecogs.com/reference/maths/differential_equations/homogeneous_differential_equations.php

Sep 12, 2011 | Toys

Press key Mode, first select option 5:EQN (by pressing key 5), then option 2: a_nX+b_nY+c_nZ=d_n (by pressin 2).

Now input coefficients from equations in table (each column is for one variable), just type in number and press =, then use arrows to move to another cell.

Now input coefficients from equations in table (each column is for one variable), just type in number and press =, then use arrows to move to another cell.

Sep 02, 2011 | Casio FX-115ES Scientific Calculator

Apply what you learned, especially that this system is quite simple.

Elimination

1. entails eliminating one variable to find (in this case) a single equation involving the other variable.

2. Solve that new equation, meaning isolate the variable that was not eliminated.

3. Substitute the value found in the last step and replace it in one of the original equation to obtain the other variable.

x+y=10

x-y=-6

Add the left sides to get x+y+x-y=2x

Add the right sides of the system to obtain 10+(-6)=4

Write Sum of left sides =Sum of right sides or 2x=4.

Since this new equation involves only x, you can solve it for x, getting x=4/2=2

Now you know the value of x (=2)

Take one of the original equations (for example x+y=10) and put 2 in place of x.

The equation becomes 2+y=10

Solve it to obtain y=10-2=8

Thus your solution is x=2, y=8

Check: use one equation in which you substitute 2 for x and 8 for y: x-y=-6 becomes 2-8=-6

Verified.

In the general case you will have to multiply by certain values to obtain opposite coefficients for the same variable. Here that was not necessary because the coefficient of y is 1 in the first equation and -1 in the second.

Elimination

1. entails eliminating one variable to find (in this case) a single equation involving the other variable.

2. Solve that new equation, meaning isolate the variable that was not eliminated.

3. Substitute the value found in the last step and replace it in one of the original equation to obtain the other variable.

x+y=10

x-y=-6

Add the left sides to get x+y+x-y=2x

Add the right sides of the system to obtain 10+(-6)=4

Write Sum of left sides =Sum of right sides or 2x=4.

Since this new equation involves only x, you can solve it for x, getting x=4/2=2

Now you know the value of x (=2)

Take one of the original equations (for example x+y=10) and put 2 in place of x.

The equation becomes 2+y=10

Solve it to obtain y=10-2=8

Thus your solution is x=2, y=8

Check: use one equation in which you substitute 2 for x and 8 for y: x-y=-6 becomes 2-8=-6

Verified.

In the general case you will have to multiply by certain values to obtain opposite coefficients for the same variable. Here that was not necessary because the coefficient of y is 1 in the first equation and -1 in the second.

Aug 16, 2011 | Casio Office Equipment & Supplies

Given "2R-3S=-10", then "6R-9S=-30".

Given "3R 2S=37", then "6R 4S=74".

Subtract the two equations: "6R-6R 4S --9S = 74 --30",

which reduces to: "4S --9S=104".

Note that 'R' has been eliminated from the equation, as requested.

Solving for 'S' is left as an exercise for the reader.

Given "3R 2S=37", then "6R 4S=74".

Subtract the two equations: "6R-6R 4S --9S = 74 --30",

which reduces to: "4S --9S=104".

Note that 'R' has been eliminated from the equation, as requested.

Solving for 'S' is left as an exercise for the reader.

Sep 03, 2010 | MathRescue Word Problems Of Algebra Lite

The newton method is used by this calculator to find the roots of equations. If you want to implement YOUR version of the Newton/Raphson algorithm, you may have to write the program yourself.

Jun 03, 2010 | Casio CFX-9850G Plus Calculator

The Solve( command can be accessed in RUN mode by pressing the OPTN button.

In the screen that is then displayed are TABS (at the bottom).

Press [F4:CALC] then [F1:Solve]

The command echoes on the screen, ready to be completed and executed.

In the screen that is then displayed are TABS (at the bottom).

Press [F4:CALC] then [F1:Solve]

The command echoes on the screen, ready to be completed and executed.

Apr 30, 2010 | Casio CFX-9850G Plus Calculator

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

213 people viewed this question

Usually answered in minutes!

×